2021
DOI: 10.1159/000516404
|View full text |Cite
|
Sign up to set email alerts
|

Response to a Combination of Full-Dose Osimertinib and Ceritinib in a Non-Small Cell Lung Cancer Patient with EML4-ALK Rearrangement and Epidermal Growth Factor Receptor Co-Mutation

Abstract: Lung cancer has been the leading cause of cancer-related deaths in both developed and developing countries, with most primary lung cancers being non-small cell lung carcinomas. Treatment for this condition is sometimes individualized. With developments in modern treatment and phase III clinical trial results, epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) and ALK-TKI have proven thier superior effectivity in comparison with the standard platinum-based doublet and are commonly approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Due to the pressure of EGFR-TKIs therapy and cloning selection, the subsequent ALK fusion gene mutations then could be detected. In the case of primary double mutation, if one of TKIs is selected for rst treatment, the remaining uninhibited mutant cell lines of ALK or EGFR will continue to grow [11]. But in the case of secondary EGFR-TKIs resistance, the need for combined application of EGFR-TKIs and ALK-TKIs may be related to the phosphorylation level of downstream proteins activated by the signaling pathway [35].…”
Section: Tumor Origin and Tumor Heterogeneity Of Egfr/alk Co-mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the pressure of EGFR-TKIs therapy and cloning selection, the subsequent ALK fusion gene mutations then could be detected. In the case of primary double mutation, if one of TKIs is selected for rst treatment, the remaining uninhibited mutant cell lines of ALK or EGFR will continue to grow [11]. But in the case of secondary EGFR-TKIs resistance, the need for combined application of EGFR-TKIs and ALK-TKIs may be related to the phosphorylation level of downstream proteins activated by the signaling pathway [35].…”
Section: Tumor Origin and Tumor Heterogeneity Of Egfr/alk Co-mutationmentioning
confidence: 99%
“…Previous studies have suggested that EGFR and ALK fusion gene mutations are independent and mutually exclusive molecular events[8] [9] [10]. But with the development and application of Next Generation Sequencing (NGS), the coexistence of EGFR-sensitive mutations and fusion mutations has been gradually con rmed by a number of case reports and clinical studies [11] [12] [13] [14] [15]. Data show that the proportion of primary EGFR mutation and ALK fusion double mutation at initial diagnosis is about 0.3-1.6%[16] [17] [18] [19], while secondary ALK fusion mutation after EGFR-TKIs application is rarely reported.…”
Section: Introductionmentioning
confidence: 99%